CHARACTERISTICS OF THE CORE METHODS OF STUDYING THE OPTIMISM OF OLDER ADOLESCENTS - Salij, Pavlo (Theoretical and Methodical Problems of Children and Youth Education, 2023)
Due to the fact that a growing personality faces many problems, crises, and developmental difficulties, the study of resource psychological and pedagogical phenomena which, contain the potential to prevent and overcome these challenges on their way to success, is extremely relevant for pedagogical science and mass educational practice. The purpose of the research is to identify the main valid methods of studying the optimism of senior teenagers in international and national studies. In accordance with the purpose, the following tasks were solved: to analyze the types and levels of psychological and pedagogical diagnostics, to identify and characterize valid methods of studying optimism. The following methods of theoretical analysis were chosen as theoretical methods: analysis of psychological and pedagogical sources on the problem, systematization, generalization and reinterpretation the results of previous studies. The empirical method was the integrated observation of the optimism diagnostics as part of a set of methods for studying the life success of senior secondary school students. The research was conducted on the Google Forms by scientists of the Laboratory of Physical Development and Healthy Lifestyle of the Institute of Problems on Education of the NAES of Ukraine. The analysis of psychological and pedagogical sources devoted to the diagnostics of optimism formation of high school students has led to the following results: the implementation of psychological and pedagogical diagnostics of participants in the educational process is recognized by researchers and practitioners as an important function of administrative and pedagogical activity and a necessary condition for the high efficiency of educational impact on students of educational institutions. This understanding leads to using diagnostics as a tool for finding ways to solve the problems of individual development of an individual or group dynamics of a certain community, finding resources to increase the effectiveness of the formation of values, virtues, qualities and characteristics of a personality that are essential for his or her successful life. Moreover, the article outlines the approaches to the organization of psychological and pedagogical diagnostics in educational institutions, provides the description of screening and in-depth diagnostics and the levels of its implementation (empirical and analytical) in the practice of the real educational process (both online and offline) of institutions of general secondary education in Ukraine. Optimism is common considered as a system of positive ideas and beliefs that have motivational and driving power and can determine a person’s life activity and success. It is considered within two main approaches: M. Seligman’s theory of attributional style and C. Carver and M. Scheyer’s concept of dispositional optimism, so its diagnosis varies depending on the author’s scientific position.